Fatigue, Fracture and Damage Analysis, Volume 1 2002
DOI: 10.1115/pvp2002-1333
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Fracture Toughness in RPV Steel Containing Segregated Zones

Abstract: Segregation zones, called ghost lines, may be present near the inner side of PWR vessel issued from plain ingots of A508 class 3 steel. They are enriched in alloying elements and impurities and may have a significant influence on mechanical properties, in particular on fracture toughness. Toughness values of a compact tension specimen containing segregation zones have been evaluated using a bimaterial model with a 3 D finite element simulation. Two fracture criteria have been tested and the results compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A 508 steel. Scatter in fracture toughness tests (Naudin et al, 2001). Equations (14) and (22) contain only two independent parameters, as shown previously.…”
Section: Small-scale Yielding Conditionsmentioning
confidence: 99%
“…A 508 steel. Scatter in fracture toughness tests (Naudin et al, 2001). Equations (14) and (22) contain only two independent parameters, as shown previously.…”
Section: Small-scale Yielding Conditionsmentioning
confidence: 99%
“…Influence of macroscopic variation was recently reported using full size vessel products and trepans from pressure vessels of decommissioned plants. Influence of macro-segregation in ingots on fracture toughness was examined in French A508 forged rings and the scatter of surveillance transition temperature shifts and some high shifts data were explained by C macro-segregation in ingots [163,164]. Other studies showed that the master curve reference temperature at the surface of unirradiated actual VVER440 pressure vessel steels was 35-70 • C lower than those of the mid-thickness region and that this difference came from the microstructural difference induced by cooling rates [165].…”
Section: Fracture Toughnessmentioning
confidence: 99%